Healing Through Interdependence: The Role of Connecting in First Nations Healing Practices - McCormick, Rod M. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study utilized the Critical Incident Technique (Flanagan, 1954), to explore the facilitation of healing for First Nations people living in the province of British Columbia. The results indicate that healing can be facilitated through practices such as connecting to family, community, spirituality, and nature. Healing approaches that help people to achieve interdependence are examined in detail as they illustrate the significant role connecting plays in First Nations healing practices. Implications for both research and practice are presented.